Africa, Brazil and Art – Persisting Challenges - Conduru, Roberto (ARS, 2021)
Analyzing works by Abdias do Nascimento, Clarival do Prado Valladares, Marianno Carneiro da Cunha, and Emanoel Araujo, among other authors, the article discusses limits and stalemates of the inclusive conception of “black art”, delineated from the 1950s, and of “Afro-Brazilian art”, consolidated from the 1980s, as well as problems posed to art historiography by the persistence of this generalizing model and the excluding character of the art circuit in Brazil, which the trajectories and works of Mestre Didi (Deoscóredes Maximiliano dos Santos) and Hélio Oiticica keep challenging.